The functional connectivity and neuropsychology underlying mental planning operations: data from the digital clock drawing test - Dion, Catherine; Tanner, Jared J.; Formanski, Erin M.; Davoudi, Anis; Rodriguez, Katie; Wiggins, Margaret E.; Amin, Manish; Penney, Dana; Davis, Randall; Heilman, Kenneth M.; Garvan, Cynthia; Libon, David J.; et al. (Frontiers in Aging Neuroscience, 2022)
We examined the construct of mental planning by quantifying digital clock drawing digit placement accuracy in command and copy conditions, and by investigating its underlying neuropsychological correlates and functional connectivity. We hypothesized greater digit misplacement would associate with attention, abstract reasoning, and visuospatial function, as well as functional connectivity from a major source of acetylcholine throughout the brain: the basal nucleus of Meynert (BNM). Participants (n=201) included non-demented older adults who completed all metrics within 24 hours of one another. A participant subset met research criteria for MCI (n=28) and was compared to non-MCI participants on digit misplacement accuracy and expected functional connectivity differences. Digit misplacement and a comparison dissociate variable of total completion time were acquired for command and copy conditions. A priori fMRI seeds were the bilateral BNM. Command digit misplacement negatively associated with semantics, visuospatial, visuoconstructional, and reasoning (p’s<0.01) and negatively associated with connectivity from the BNM to the anterior cingulate cortex (ACC; p=0.001). Individuals with MCI had more misplacement and less BNM-ACC connectivity (p=0.007). Total completion time involved posterior and cerebellar associations only. Findings suggest clock drawing digit placement accuracy may be a unique metric of mental planning and provide insight into neurodegenerative disease.